Aetiology, presentation and outcomes of patients presenting with acute pancreatitis in a tertiary care hospital - Zahabia Sohail; Hafsa Shaikh; Nimra Iqbal; Hassan Musood; Om Parkash (Journal of the Pakistan Medical Association, 2024)
Acute pancreatitis (AP) is a multi-causal disease with a high rate of hospitalisation. Only a few clinical studies have investigated the aetiological background, severity, and outcome of AP in Pakistan. Hence, this study was carried out to determine the aforementioned factors and correlate them with outcomes in a tertiary care setting. This was a cross-sectional, retrospective study conducted at the Department of Gastroenterology, Aga Khan University Hospital, Karachi, from January 1, 2022, to December 31, 2022. Data was analysed using statistical software SPSS version 25. Vomiting was the predominant presenting complaint and was seen in 139 (78.5%) patients. Gallstones were the predominant cause in 68 (37%) patients, followed by idiopathic pancreatitis in 22 (12%) patients. Thirteen (7.1%) patients passed away. Patients with systemic complications were likely to suffer from severe disease (p=0.02), whereas those with local complications were at an increased risk of mortality (p=0.04). —Continue